Polyporaceae lignosus rhinocerus TM02® cultivar as complementary therapy for respiratory health: a preliminary investigation of asthma - Poh, Mau Ern; Mohamad Razif, Muhammad Fazril; Zainal Abidin, Muhammad 'Adil; Liam, Chong Kin; Pang, Yong Kek; Yeoh, Kee Ying; Sia, Leng Cheng; Ibrahim, Nur Husna; Wong, Chee Kuan; Tan, Jiunn Liang; Loh, Thian Chee; Munusamy, Vijayan; et al. (Elsevier B.V., 2025)
Lignosus is a genus of polypore fungi, commonly known as Tiger Milk mushroom (TMM), that has long been valued for its beneficial medicinal properties. TMM are traditionally used by the native communities of Southeast Asia, particularly Malaysia, to alleviate various illnesses, including cough and asthma. L. rhinocerus TM02®, a cultivated strain of L. rhinocerus (Cooke) Ryvarden, has been shown to possess antioxidant, immunomodulatory, and bronchodilatory properties. This study aims to investigate the efficacy of L. rhinocerus TM02® supplementation in relieving symptoms and reducing airway inflammation in participants with uncontrolled asthma. The effects of TM02® supplementation on bronchodilation were determined via trough forced expiratory volume in 1 second (FEV1) measurements, serial measurements of fractional exhaled nitric oxide (FeNO) levels, blood eosinophil count, and serum immunoglobulin E (IgE) and assessed using the Asthma Control Questionnaire-7 (ACQ-7). After 90 days of supplementation, the overall mean FEV1 significantly increased by 0.3 L (p<0.001), with improvements in asthma control demonstrated by a reduction in ACQ-7 scores (p<0.001). FeNO, blood eosinophil count, and serum IgE levels showed significant reductions (p<0.001). Overall, our findings suggest that L. rhinocerus TM02® holds promise as a potential supplement to support overall respiratory health.